KEPEMIMPINAN KEPALA SUKU PADA SUKU LANI DI DESA YOWO DISTRIK KEMBU KABUPATEN TOLIKARA - Enembe, Yoiles; Deeng, Djefry; Mawara, Jetty E. T. (Universitas Sam Ratulangi, 2018)
People are associated with one another and environment. Lifelike clusters of both the large and small group. The relationship pattern give birth to the concept of leadership. Leadership is needed by man for set and take care of the dynamics of community itself.In some rural communities, in addition to government leadership formal kind the village head, too to know the leadership of informal or leadership is not official. Even though called leadership is not official, but sometimes in his leadership is a big influence or stronger in society than formal leader.Methods used in this research namely qualitative descriptive. The qualitative method as procedure research that yields data in the form of descriptive of words written or spoken of other people and of observable behavior.Change or shifts more is visible on several institutions culture, like the, livelihoods, art, language caused by the contact with culture outside. Change or shifts in a systems and the role in leadership, this seen when held discussions and interviews with some high-profile figures in society, no openness full and maintain the certain information that should not be known by clan other.Unity live which is in a bond kinship in the form of each clan, but by the dutch government then combined (rivers with and the bottom) into one community. So the leadership on the head clan reduced but in fact located Lani leadership.Â Keywords : leadership, tribe, clan